Upgrading in design scheme of Unit Kesihatan Universiti Teknologi Mara (UiTM) Perak at Universiti Teknologi Mara (UiTM) Perak, Seri Iskandar Campus, 32600 Bota, Perak Darul Ridzuan / Nur 'Aima Mazlan - Mazlan, Nur 'Aima (Faculty of Architecture, Planning and Surveying, 2011)
This final project is a manifestation of Diploma Interior Design students' understanding of all aspects of interior design that has been learned from the foundation to the design of the final proposal project. This project is about to upgrading new interior design scheme of Unit Kesihatan for Universiti Teknologi MARA (UiTM) Perak. The client of this project is Unit Kesihatan UiTM Perak. The reason to propose this project is because Unit Kesihatan is the one of important department at UiTM Perak. Unit Kesihatan are the nearest medical centre provided for student’s in UiTM Perak to get medical treatment if they get sick. However, I found there are some problems and need solutions. The research will involved research methodology such as observation, interview, internet, experienced and side references conducted. For this project, I’m just use the existing site because the location is strategic and easy to come.The objective is to create a health center in a systematic order to facilitate all matters because the public knows that the health center always receive patients especially the visitor.